Intellectual muslim responses to the ideas of feminism in the post-Suharto era - Amin Fauzi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This study examines the responses of Indonesian Muslim intellectuals to the ideas of feminism in the post-Suharto era. This study seeks to understand the proponents' as well the opponents' ideas of feminism — such as gender, equality, patriarchy, misogyny and their relationship with secularism, pluralism, and liberalism. It also analyses the relationship between feminism and gender issues with the orientation of Islamic studies and the interpretation of Islamic law which involves women such as in inheritance, the right of divorce, marriage with the non-Muslim, guardian of marriage, to be witness in court, leadership, polygamy, etc.. Lastly, it highlights the points of agreement and disagreement between the proponents and opponents of feminism. This research is methodologically qualitative, involving library research and accomplished by field work for an extended period in Indonesia to gather the necessary data and to gain information as well as clarifications or responses from the primary sources, namely the scholars, intellectuals, and intelligentsia involved in the feminist discourse or its responses. This study reveals that there is a diversity of response among Indonesian Muslim scholars on the issue of feminism. There are Muslim intellectuals, either individually or collectively, coming from Muslim NGOs or institutions who supported and even promoted such an idea and made it the framework in understanding Islam on gender issues. They are popularly called “Muslim liberals” or “Muslim feminists”. On the other side, there are Muslim intellectuals who opposed such ideas either comprehensively or accepted them conditionally as long as they are compatible with the Islamic worldview and in line with Islamic principles and values. The study shows that the discourse of feminism in post Suharto Era is not inseparable from the orientation of Islamic studies in the institution of Indonesian higher learning — especially IAIN/UIN — and the specific trends of Islamic thought which were developed and promoted by individual Muslim scholars. Such trends promoted the agenda to “integrate” or “synthesize” Islamic traditional sciences — such as tafsÊr, ÍadÊth, Islamic jurisprudence, kalÉm (theology) — and contemporary social sciences and humanities which were coloured by the paradigm and values of modernism and postmodernism. As a result, there arose several ideas which were found to be contrary to SharÊ'ah and mainstream Islamic positions on gender issues. This study finally suggests that the orientation of Islamic studies generally and gender issues particularly, should do justice to tawhidic Islamic worldview, principles, and values, although on new issues not covered by authoritative revealed texts, the exercise of ijtihÉd is to be encouraged. At the same time, it should also be critical in assessing Western thought either from modernism or postmodernism.